2023
DOI: 10.2174/1568009622666221010105701
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Core 1 Beta 1, 3-Galactosyltransferase Suppresses Osteosarcoma Growth with Induction of IFN-γ Secretion and Proliferation of CD8+ T Cells

Abstract: Purpose: Abnormal glycosylation often occurs in tumor cells. T-synthase (core 1 beta 1,3-galactosyltransferase, C1GALT1, or T-synthase) is a key enzyme involved in O-glycosylation. Although T-synthase is known to be important in human tumors, the effects of T-synthase and T-antigen on human tumor responses remain poorly defined. Methods: In this study, a T-synthase-specific short hairpin RNA (shRNA) or T-synthase-specific eukaryotic expression vector(pcDNA3.1(+)) was transfected into murine Osteosarcoma LM8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Up-regulation of C1GALT1 promotes the proliferation of osteosarcoma cells in vitro but exhibits a significant growth inhibitory effect after 3 weeks post-implantation in xenograft models in vivo . These effects could be explained by the fact that high C1GALT1 expression stimulated CD8+ T-cell proliferation and the increased production of IFN-γ by CD4+ T cell, inducing enhanced tumor lethality of Cytotoxic T lymphocytes (CTLs) and improving anti-tumor immunity [ 182 ]. Further studies on C1GALT1 activity in osteosarcoma are necessary to clarify its role.…”
Section: Glycosylationmentioning
confidence: 99%
“…Up-regulation of C1GALT1 promotes the proliferation of osteosarcoma cells in vitro but exhibits a significant growth inhibitory effect after 3 weeks post-implantation in xenograft models in vivo . These effects could be explained by the fact that high C1GALT1 expression stimulated CD8+ T-cell proliferation and the increased production of IFN-γ by CD4+ T cell, inducing enhanced tumor lethality of Cytotoxic T lymphocytes (CTLs) and improving anti-tumor immunity [ 182 ]. Further studies on C1GALT1 activity in osteosarcoma are necessary to clarify its role.…”
Section: Glycosylationmentioning
confidence: 99%
“…The infiltration of CD8 positive lymphocytes was significantly associated with improved survival in osteosarcoma patients treated with zoledronic acid, suggesting a positive immunoregulatory role of CD8 positive lymphocytes in inhibiting osteosarcoma growth and metastasis ( Gomez-Brouchet et al, 2017 ). Research by Tang et al revealed that upregulation of T-synthase in osteosarcoma enhances CD8 + T cell proliferation and function, thereby inhibiting tumor growth, while CD4 + T cells exert a suppressive effect on tumor cells through IFN-γ secretion ( Tang et al, 2023 ). Moreover, the combined administration of IDO inhibitors and platinum(IV) prodrugs initiated the cGAS-STING pathway, enhancing CD8 + T cell function, which correlated with a more effective immune response and chemotherapy outcome, demonstrating potential in inhibiting tumor proliferation and dissemination ( Xiang et al, 2023 ).…”
Section: Immune Cellsmentioning
confidence: 99%